Understanding public perceptions of biotechnology through the "Integrative Worldview Framework". (January 2017) - De Witt, Annick; Osseweijer, Patricia; Pierce, Robin
Biotechnological innovations prompt a range of societal responses that demand understanding. Research has shown such responses are shaped by individuals' cultural worldviews . We aim to demonstrate how the Integrative Worldview Framework (IWF) can be used for analyzing perceptions of biotechnology, by reviewing (1) research on public perceptions of biotechnology and (2) analyses of the stakeholder-debate on the bio-based economy, using the Integrative Worldview Framework (IWF) as analytical lens. This framework operationalizes the concept of worldview and distinguishes between traditional, modern, and postmodern worldviews, among others. Applied to these literatures, this framework illuminates how these worldviews underlie major societal responses, thereby providing a unifying understanding of the literature on perceptions of biotechnology. We conclude the IWF has relevance for informing research on perceptions of socio-technical changes, generating insight into the paradigmatic gaps in social science, and facilitating reflexive and inclusive policy-making and debates on these timely issues.